MEDIA SOSIAL EDMODO UNTUK MENGEMBANGKAN KETERAMPILAN ARGUMENTASI MAHASISWA PROGRAM STUDI NON SAINS - Ipah Budi Minarti (Universitas PGRI Semarang, 2015)
The research was conducted to develop students argumentation skills through the utilization of social media Edmodo. The utilization of social media Edmodo was expected to treat students in forming a claim that was supported by the evidence and guarantees opinion to support the claim. The subjects of this study were the fourth semester students of academic year 2013/2014 in the University of PGRI Semarang as much as 3 classes (42 students per class) that follow the lecture of Natural Science Basis. Quantitative data of student argumentation skills was acquired through the assessment of the arguments quality by using the assessment instrument arguments rubric. The results showed that the use of social media Edmodo improved the student argumentation skills. Limited time in exercising the student argumentation skills in the class can be resolved with the interaction of students in solving problems which posted online. The quality of the student's argument can be seen from the most of the students were at level 2, 3, and 4. This indicated that the student has been able to establish a claim supported by the evidence and guarantees opinions to support the claims that have been made. Keywords: argumentation skills of students, social media Edmodo